ŠEST MODALITETA UTICAJA MEĐUNARODNOG PRAVA NA KRIVIČNOPRAVNU ZAŠTITU ŽIVOTNE SREDINE - Aleksandar Todorović (Revija za kriminologiju i krivično pravo)
The subject of analysis in this paper are issues concerning the possible modalities of the influence of international law on the protection of the environment through criminal law, regardless of whether such protection is provided at the international or national level. The expertcritical analysis of the literature collected for the purpose of addressing the issues that constitute the content of this paper shows six modalities of the influence of international law on the protection of the environment through criminal law. These are: Complete international legal modality, General hybrid modality, Specific hybrid modality, Modality of indirect intervention in the national legal order, Modality of reference to international law, and Modality of supranational influence. Each of the six possible modalities of the influence of international law on the protection of the environment through criminal law, as a universal human value, is presented in the paper through the analysis of their essential characteristics, individually and with special emphasis on their specific characteristics that formed the basis of the classification of the modalities. Moreover, the research conducted for the purposes of this paper is based on three methods (normative, comparative, and historical), where the legal system of the Republic of Serbia (primarily its criminal legislation) was used as the basis of comparison, where appropriate. At the end of the paper, the author, among other things, points out the necessity of expanding research on the subject matter. The key reason for the necessity of such an approach to this issue lies, according to the author, in the fact that there is a disproportion between its theoretical treatment and the degree of its importance for the desired level of protection of the environment through criminal law as an ultima ratio means. Viewed in this context, the author, among other things, points out the possibility of expanding research on situations where international law affects the immediate legal protection another good, not the environment, but the protection of that other good through criminal law protects the environment as well. The author preliminarily designates this type of influence as an “incidental” modality of influence. According to the author, the same applies to the procedural aspect of the protection of the environment through criminal law, such as international cooperation in the detection and prosecution of perpetrators or issues related to jurisdiction in criminal offenses where pollution has a cross-border effect or is committed outside state territory (e.g. on the open sea ).